Bacolet House, Tobago - (:unkn) unknown (My University, 2010)
A hotel in Tobago.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Guesthouses--Trinidad and Tobago--Tobago